Adverse events of bevacizumab for triple negative breast cancer and HER-2 negative metastatic breast cancer: A meta-analysis - Xun, Xueqiong; Ai, Jun; Feng, Fuhui; Hong, Pan; Rai, Saroj; Liu, Ruikang; Zhang, Baowen; Zhou, Yeming; Hu, Huiyong (Frontiers in Pharmacology, 2023)
Abstract: Background: triple-negative breast cancer (TNBC) and HER-2 negative metastatic breast cancer (HER-2 negative MBC) are intractable to various treatment schemes. Bevacizumab as a novel anti-VEGF drug, its safety for these two high-risk breast cancers remains controversial. Therefore, we conducted this meta-analysis to assess the safety of Bevacizumab for TNBC and HER-2 negative MBC. Methods: We searched Medline, Embase, Web of science and Cochrane databases updated to Oct 1st, 2022 for relevant randomized controlled trials (RCTs). In all, 18 RCTs articles with 12664 female patients were included. We used any grade Adverse Events (AEs) and grade ≥ 3 AEs to assess the AEs of Bevacizumab. Results: Our study demonstrated that the application of Bevacizumab was associated with increased incidence of grade ≥ 3 AEs (RR=1.37, 95% CI 1.30-1.45, Rate: 52.59% vs 41.32%). Any grade AEs (RR=1.06, 95%CI 1.04-1.08, Rate: 64.55% vs 70.59%) did not show a significant statistical difference in both overall results and among the subgroups. In subgroup analysis, HER-2 negative MBC (RR=1.57, 95% CI 1.41-1.75, Rate: 39.49% vs 25.6%), dosage over 15mg/3w (RR=1.44, 95% CI 1.07-1.92, Rate: 28.67% vs 19.93%) and endocrine therapy (ET) (RR=2.32, 95% CI 1.73-3.12, Rate: 31.17% vs 13.42%) were associated with higher risk of grade ≥ 3 AEs. Of all graded ≥ 3 AEs, proteinuria (RR=9.22, 95%CI 4.49-18.93, Rate: 4.22% vs 0.38%), mucosal inflammation (RR=8.12, 95%CI 2.46-26.77, Rate: 3.49% vs 0.43%), palmar-plantar erythrodysesthesia syndrome (RR=6.95, 95%CI 2.47-19.57, Rate: 6.01% vs 0.87%), increased Alanine aminotransferase (ALT) (RR=6.95, 95%CI 1.59-30.38, Rate: 3.13% vs 0.24%) and hypertension (RR=4.94, 95%CI 3.84-6.35, Rate: 9.44% vs 2.02%) had the top 5 risk ratios. Conclusion: The addition of Bevacizumab for TNBC and HER-2 negative MBC patients showed an increased incidence of AEs especially for grade ≥ 3 AEs. The risk of developing different AEs varies mostly dependent on the type of breast cancer and combined therapy.